2007
DOI: 10.1002/mc.20287
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C δ enhances proliferation and survival of murine mammary cells

Abstract: Protein kinase C (PKC) delta, a member of the novel family of PKC serine-threonine kinases, has been implicated in negative regulation of proliferation and apoptosis in a large number of cell types, including breast cancer cell lines, and postulated as a tumor suppressor gene. In this study we show that in murine NMuMG mammary cells PKCdelta promotes a mitogenic response. Overexpression of PKCdelta in NMuMG cells leads to a significant increase in [3H]-tymidine incorporation and cell proliferation, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 50 publications
(59 reference statements)
2
78
0
1
Order By: Relevance
“…PI 3-kinase-dependent activation of Akt is mediated by PKC-␦, which is required for cell survival in various cancer and immune cells (1,2,28). However, Zhong et al suggested that PKC-␦ downregulation suppresses apoptotic signals through a novel PI 3-kinase-independent survival pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…PI 3-kinase-dependent activation of Akt is mediated by PKC-␦, which is required for cell survival in various cancer and immune cells (1,2,28). However, Zhong et al suggested that PKC-␦ downregulation suppresses apoptotic signals through a novel PI 3-kinase-independent survival pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of PKCδ in estrogen-responsive tissues have been contradictory. PKCδ increased proliferative and survival capacities in an immortal- ized mammary cell line (23). Estrogen has been reported to stimulate the expression of PKCδ in the corpus luteum (24), but to downregulate the expression of PKCδ in MCF-7 cells (20).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, there is a substantial body of evidence linking PKC to the initiation and progression of certain types of cancers, including gliomas, and breast, pancreatic and colon cancers (Alonso-Escolano et al, 2006;Bredel and Pollack, 1997;El-Rayes et al, 2008;Gokmen-Polar et al, 2001;Grossoni et al, 2007). Total PKC expression and activity levels are significantly higher in normal brain tissue than in non-brain tissues, suggesting that this serine/threonine kinase has a fundamental role in normal brain physiology (Nelsona and Alkona, 2009;Steinhart et al, 2007).…”
Section: Introductionmentioning
confidence: 99%